'The voice is the guide to the experience as well as the experience itself': An interview with non zero one. Issue 1 (1st January 2016) - Thomaidis, Konstantinos; Butcher, Sarah
Since 2009, non zero one – a London-based collective of artists with a background and interest in theatre but working across media and performance disciplines – has devised a series of unexpected, challenging but also light-hearted and inviting experiences of immersion. Whilst embracing a variety of techniques and contemporary media, one of the key features of the company's work is the exploration of audience interaction through the use of headphones, typically in promenade and/ or site-specific performance contexts. Following a first section that questions the role of voice in (theatrical) sonic immersion, the text unfolds as a dialogue between practitioner-scholar Konstantinos Thomaidis and non zero one artist and theatre director Sarah Butcher. The interview lends an attentive ear to the role of voice in the company's work, from pre-recorded instruction to live audio interaction.